2021
DOI: 10.1016/j.eats.2020.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Failed Type V Acromioclavicular Separation Due to Coracoid Fracture: Revision of Acromioclavicular-Coracoclavicular Reconstruction and Coracoid Fixation

Abstract: Acromioclavicular (AC) injuries are common, especially in the young and active population. AC joint dislocations account for 8% of all joint dislocations and are even more common in contact sports. These injuries are graded as type I through type VI on the basis of the Rockwood classification method. Types I and II are generally treated without surgery whereas types IV, V, and VI are best treated operatively. Type III dislocations remain controversial in terms of treatment, and many surgeons recommend nonopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…3 Nondisplaced and minimally displaced fractures are primarily treated conservatively while concomitant and displaced fractures are more likely to be treated surgically; however, specific surgical indications and techniques have not been clearly established. 2,4 Patients with a coracoid fracture will typically present with pain in the region of the infraclavicular fossa, and in the case of an isolated fracture, will likely have pain over the coracoid; however, coracoid fractures can receive delayed diagnoses due to the common presence of concomitant injuries, which may overshadow the fracture. 2,5 In this case of an isolated fracture, the surgeon performed a focused exam, which elicited pain over the coracoid and not the AC joint.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nondisplaced and minimally displaced fractures are primarily treated conservatively while concomitant and displaced fractures are more likely to be treated surgically; however, specific surgical indications and techniques have not been clearly established. 2,4 Patients with a coracoid fracture will typically present with pain in the region of the infraclavicular fossa, and in the case of an isolated fracture, will likely have pain over the coracoid; however, coracoid fractures can receive delayed diagnoses due to the common presence of concomitant injuries, which may overshadow the fracture. 2,5 In this case of an isolated fracture, the surgeon performed a focused exam, which elicited pain over the coracoid and not the AC joint.…”
Section: Discussionmentioning
confidence: 99%
“…Drill holes through the clavicle and/or coracoid serve as stress risers, which may cause the construct to fail as a result of conjoined tendon tears, fracture, or cutout. 21,22 A biomechanical study by Martetschläger et al 23 that examined the effect of coracoid drilling in 18 fresh-frozen cadaveric scapulae following anatomic CC ligament reconstruction found that single drill holes of 2.4 mm resulted in greater load to failure than one or two 4-mm drill holes (506 AE 73.3 N for one 2.4-mm tunnel vs 392 AE 98.2 N for two 4-mm tunnels, and 459 AE 143.8 N for one 4-mm tunnel, P ¼ .015). The mechanism of failure in all specimen was fracture of the coracoid process.…”
Section: Discussionmentioning
confidence: 99%